Incidence, immediate consequences, associated factors and health-seeking behaviour related to falls among the elderly in Elapatha Medical Officer of Health Area, Sri Lanka - B. M. I. Gunawardana; R. D. S. Ranasinghe (College of Community Physicians of Sri Lanka, 2021)
Introduction: Older adults are more vulnerable to falls, which are the most common cause of mortality and morbidity in the elderly. The consequences of falls and its health seeking behaviour will affect the quality of life of the elderly.   Objectives: To describe the incidence, immediate consequences, associated factors and health-seeking behaviour related to falls among the elderly in Elapatha Medical Officer of Health (MOH) Area.   Methods: A community-based cross-sectional study was conducted in Elapatha MOH Area. Cluster sampling technique was used to select 510 elderly using probability proportional to the size of the population technique. Retrospective data on falls during the previous three months were collected using an intervieweradministrated questionnaire.   Results: Cumulative incidence of falls during the past three months was 127 (95% CI=100, 159) falls per 1000 elderly. Older age (75 years and above) (adjusted odds ratio (aOR)=3.4; 95% CI=1.4, 8.4) being a female (aOR=2.1; 95% CI=1.2, 3.8) and elders who were currently employed (aOR=3.6; 95% CI=1.9, 6.9) were positively associated with falls in binary logistic regression analysis. No significant associations were observed with the level of education, living alone and the marital status. The higher proportion of falls (n=38; 59.4%) were due to Hazardous environmental conditions. Injurious falls occurred in 35.9% (n=23) of cases. Most (n=12; 41.4%) of the fall victims had received Western treatment.   Conclusions & Recommendations: There was a higher reported incidence of falls among the elderly population specially among the female gender and the elders who were currently employed. Thus, there is a need for strengthening of awareness programmes on prevention of falls among elderly population and incorporation of elderly risk assessments in the available national screening programmes is a timely need.